2015
DOI: 10.1093/cid/civ1033
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Refractory Otomastoiditis Due to Nontuberculous Mycobacteria: Institutional Experience and Review of the Literature

Abstract: NTM otomastoiditis should be suspected if a patient has chronic refractory otorrhea and ear granulation tissue. Surgery, which is the mainstay of treatment, should be complemented with antibiotics. In those without temporal bone osteomyelitis, antibiotic treatment can be stopped after a dry ear is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…This was subsequently confirmed as MAI. Although granuloma is a characteristic histopathologic finding, granulation as seen in our patient has previously been reported in infections with M. marinum , M. abscessus , M. chelonae , M. fortuitum, MAI, and other NTMs . Esophageal mycobacterial diseases could be managed with antibiotics alone or in combination with adjunct surgery (Table ).…”
Section: Discussion and Literature Reviewsupporting
confidence: 52%
“…This was subsequently confirmed as MAI. Although granuloma is a characteristic histopathologic finding, granulation as seen in our patient has previously been reported in infections with M. marinum , M. abscessus , M. chelonae , M. fortuitum, MAI, and other NTMs . Esophageal mycobacterial diseases could be managed with antibiotics alone or in combination with adjunct surgery (Table ).…”
Section: Discussion and Literature Reviewsupporting
confidence: 52%
“…Yeh et al . discussed the fact that NTM otomastoiditis with TBO should be suspected in cases of chronic otorrhoea, otalgia and granulation tissue in the ear [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case series has reported the rates of granulation tissue (90.9 %), otalgia (31.8 %), facial palsy (9.1 %) and lung involvement (5.4 %). Cases of temporal bone osteomyelitis have been reported, most commonly with the NTM M. abscessus (52.7 % of cases) and M. aviumintracellulare, followed by M. fortuitum [21][22][23]. Three distinct routes have been suggested for the entry of NTM into the middle ear: direct inoculation through perforation of the tympanic membrane or a tympanostomy tube (most common), through the eustachian tube, and direct spread via improperly sterilized surgical instruments [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we described a case of local temporal bone osteomyelitis caused by granulomatous tuberculous infection [22]. Yeh et al reported that in case of chronic otorrhea, otalgia, and granulation tissue in the ear a diagnosis of otomastoiditis with TBO caused by nontuberculous Mycobacteria should be suspected [23]. The authors concluded that acid-fast stain and mycobacterial culture should be performed in all suspicious cases.…”
Section: Discussionmentioning
confidence: 99%